An optimization of tin plating process using design of experiment - Lazim, Azrina (2008)
This research was done to reduce the variation of coating weight in Tin plating process. The objective of this research is to find the optimum setting in tin plating process. Design of Experiment was used to analyze varies combination of process parameters. The process parameters investigated were Speed, Temperature, Sodium Ferrocynide and Mole ratio fluoride to total stannous. It was not economically practical to run experiments in the real life factory environment as such historical data was used in this study. The historical data were selected to match the 24 full factorial of design matrix. Any missing data were treated by using regression method. The study reveals that the optimum setting is the high value (+1) of Speed, Sodium Ferrocynide and Mole ratio fluoride to total stannous. Mathematical model is proposed to predict the performance of plating process with coating weight as the response. The model is valid within the investigated ranges and other experiments were conducted to analyze the characteristics of tin plate. The experiments are surface roughness test, surface topography, and cross section analysis. There are a few suggestions and suitable action plan were proposed to increase the quality of production.